2008
DOI: 10.1007/s11095-008-9626-z
|View full text |Cite
|
Sign up to set email alerts
|

Shape Induced Inhibition of Phagocytosis of Polymer Particles

Abstract: Shape-induced inhibition of phagocytosis of drug delivery particles is possible by minimizing the size-normalized curvature of particles. We have created a high aspect ratio shape that exhibits negligible uptake by macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
430
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 553 publications
(449 citation statements)
references
References 10 publications
18
430
0
1
Order By: Relevance
“…The engulfment of cylindrical parƟcles was observed to take place from the ends without excepƟon (Fig. 1), supporƟng the paradigm that phagocytosis is highly orientaƟon and shape dependent [1,2,4]. This means that the geometry at the point of first contact between the macrophage and the parƟcle governs the iniƟaƟon of phagocytosis.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The engulfment of cylindrical parƟcles was observed to take place from the ends without excepƟon (Fig. 1), supporƟng the paradigm that phagocytosis is highly orientaƟon and shape dependent [1,2,4]. This means that the geometry at the point of first contact between the macrophage and the parƟcle governs the iniƟaƟon of phagocytosis.…”
Section: Resultsmentioning
confidence: 94%
“…This shapeinduced delay of internalizaƟon extends the residence Ɵme of the carrier system, represenƟng a new design parameter for the retardaƟon of clearance [4]. The nature of the used parƟcles dictates the condiƟons of release, either within the phagocyte or before internalizaƟon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages, an essential component of the immune system, play a major role in governing the fate of polymeric particles administered into the body for drug delivery or diagnostic applications (23)(24)(25). It has been shown that particles with high AR, such as EDs, have the potential to mitigate phagocytosis (26). We hypothesized that the ability of particles to switch shapes may be used to achieve precise control over the extent and duration of mitigation of phagocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that departure from the conventional spherical shape of particles brings unique and improved functionalities to the particulate systems, resulting in improved biological responses. For example, macrophage-mediated phagocytosis is governed by the local geometry of the particles (40), and elongated particles exhibit reduced phagocytosis, longer circulation in the blood, and higher accumulation in target tissues (26,32,34,41). The same shape, however, impedes particle internalization into target cells compared to spheres (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%